Antecedent and Consequences of Risk Perception on Tourist Decision Making towards the Sustainable Medical Tourism Development in Bangladesh - Polas, Mohammad Rashed Hasan; Sahidullah, Mohamad; Hossain, Mohammad Imtiaz; Karim, Asif Mahbub; Prabhakaran, Sudesh; Khan, Arif Md (Journal of Tourism Management Research, 2019)
In order to learn more about the antecedents and consequences of tourist decision making in the medical tourism industry, this study reveals how risk perception influences the tourist decision making of medical tourism development. Then, we test the hypothesis by collecting survey data of 226 from respondents of different hospitals at Dhaka in Bangladesh who came for medical treatment there. Moreover, we hypothesize that tourist experience, tourist attitude, and media influence increases tourist decision making with the mediating effect of risk perception. The findings confirm a positive significant relationship between tourist experience and media influence on risk perception. A positive direct relationship between media influence and tourist decision making was also found. Then, we examine how risk perception mediates this relationship with tourist decision making which is found positive. However, this study didn’t find any significant relationship between tourist attitude and risk perception, in contrast with the earlier findings. Our results extend previous research by not only highlighting the importance of medical tourism in shaping the host destination’s strategic behavior but also indicating how each dimension of medical tourism influences on enhancing the tourist decision.